2013
DOI: 10.5194/bg-10-2451-2013
|View full text |Cite
|
Sign up to set email alerts
|

A data assimilation framework for constraining upscaled cropland carbon flux seasonality and biometry with MODIS

Abstract: Agroecosystem models are strongly dependent on information on land management patterns for regional applications. Land management practices play a major role in determining global yield variability, and add an anthropogenic signal to the observed seasonality of atmospheric CO2 concentrations. However, there is still little knowledge on spatial and temporal variability of important farmland activities such as crop sowing dates, and thus these remain rather crudely approximated within carbon cycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…This research demonstrates the value of the Sentinel-2 spectral characteristics for retrieving critical variables that can support more sustainable crop management practices. the value of LAI data for updating state variables in process-based agroecosystem models in order to improve estimates of crop yield [3][4][5][6] and land-atmosphere carbon dioxide exchanges [7,8]. On the other hand, chlorophyll is a key driver of plant light absorption and conversion to chemical energy and is, therefore, an indicator of plant health and potential gross primary productivity [9,10].…”
mentioning
confidence: 99%
“…This research demonstrates the value of the Sentinel-2 spectral characteristics for retrieving critical variables that can support more sustainable crop management practices. the value of LAI data for updating state variables in process-based agroecosystem models in order to improve estimates of crop yield [3][4][5][6] and land-atmosphere carbon dioxide exchanges [7,8]. On the other hand, chlorophyll is a key driver of plant light absorption and conversion to chemical energy and is, therefore, an indicator of plant health and potential gross primary productivity [9,10].…”
mentioning
confidence: 99%
“…However, crops are highly diverse in terms of both species grown and management practices applied. Accordingly, previous studies showed that crop parameters are critical to transfer to other sites [ Sus et al, ] or different resolutions [ Iizumi et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The GPP data does not have an estimate of the uncertainty about that data and so instead we infer the uncertainty associated 10 with that data as σ x,D . In the case of MODIS fAPAR data we explicitly incorporate a measure of variation in the data within the geographical area used to compute the mean fAPAR as well as inferring a parameter representing additional unexplained variation.…”
Section: Parameter Estimation Techniquementioning
confidence: 99%
“…The second data source is flux tower eddy covariance (EC) data which provides high resolution CO 2 fluxes 15 at point locations (Baldocchi and Wilson, 2001). Previously, data assimilation methods have been used for an ecosystem model in croplands with earth observation data (Revill et al, 2013;Sus et al, 2013), but both studies focused on ecosystem carbon fluxes and leaf area index and included no estimates of yield.…”
Section: Introductionmentioning
confidence: 99%